The Effect of Free Shipping, Online Customer Review, Online Promotion, And Flash Sale on Purchase Decisions n Shopee E-Commerce - Rizky Aprillia Damayanti; Sri Nawangsari (Economic Reviews Journal, 2025)
The purpose of this study is to analyze the effect of free shipping, online customer review, online promotion, and flash sale on purchase decisions in Shopee e-commerce both partially and simultaneously. The analytical methods used are: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t-test, f-test, and coefficient of determination. The testing tool used is SPSS. The data used in this study uses questionnaires distributed to 150 respondents. The testing tool used is SPSS. The results show that partially, free shipping variables, online customer review, and online promotion affect purchase decisions, while flash sale variables do not affect purchase decisions. Meanwhile, simultaneously, free shipping variables, online customer review, online promotion, and flash sale affect purchase decisions.